Effects of think-pair-share and numbered heads together teaching strategies on junior secondary school students’ achievement in mathematics in South west Nigeria (2021)
Mathematics is one of the core subjects both at primary and secondary school levels in Nigeria. The importance accorded to mathematics in the curriculum reflects the recognition of its vital role towards national and technological development and the role it plays in contemporary society. Despite the importance of Mathematics to societal development, it is a subject that many students dislike and fail. Therefore the issue of poor achievement of students in Mathematics has become a perennial problem in Nigeria. The persistent failure of students has remained a major concern to Mathematics educators. This calls for strategies that will create hands-on/mind-on learning activities such as Think-Pair-Share and Numbered Heads Together Teaching strategies. This study therefore determined the effect of Think-Pair-Share and Numbered Heads Together Teaching strategies on students’ achievement in Mathematics. The moderating effect of mental ability and gender influence on students’ achievement in Mathematics are also examined. The study adopted pretest-posttest control group quasi-experimental research design. Intact classes of JS2 comprising of 310 students from six purposively selected secondary schools in Osun west senatorial district of Osun state, Nigeria were the participants of the study. The schools were randomly assigned to treatment of Think-Pair-Share, Numbered Heads Together and conventional teaching strategies. Seven instruments were used to gather data for the study and seven null hypotheses were formulated and tested at 0.05 level of significance. Data were analysed using Analysis of Covariance and Scheffe post-hoc analysis. Treatment had significant main effect on students’ achievement in Mathematics. There was no significant main effect of mental ability and gender on students’ achievement, likewise two-way interaction effect. However, three-way interaction effect is significant. The study therefore recommends that Mathematics teachers in secondary schools should adopt Think-Pair-Share and Numbered Heads Together Teaching strategies for improving achievement in Mathematics. Government should retrain secondary school teachers on how to use Think-Pair-Share and Numbered Heads Together Teaching strategies. Also curriculum planners and experts in Mathematics should design curricular that are student activity-based.